Horizontal vibration response analysis of piles in liquefied soil under Winkler foundation model - XIONG Hui; YANG Feng (Rock and Soil Mechanics, 2020)
By considering the condition of vertical load, the soil after complete liquefaction is regarded as fluid, and the pile foundation is equivalent to the Euler-Bernoulli beam model. The vibration impedance of the top of the pile foundation embedded in the pile bottom is discussed. Simulating liquefied soil using fluid dynamic equation and simulating lower non-liquefied soil layer with Winkler foundation, combined with the continuous conditions of displacement, rotation angle and internal force at the interface between the liquefied soil and the non-liquefied soil, the relationship between displacement and internal force expression of pile’s top and pile’s bottom is obtained by means of the matrix transfer method. Finally, according to the embedded conditions at the bottom of the end bearing pile, the expression of the impedance of the pile’s top is obtained. Compared with the existing literature, the correctness of the paper is verified. The parameter analysis of the impedance influence conditions shows that the liquefaction depth, the pile’s top axial force and the fluid density have different effects on the impedance of the pile’s top.